Protracted maritime boundary disputes and maritime laws. Issue 2 (8th February 2019) - Hasan, Md. Monjur; Jian, He; Alam, Md. Wahidul; Chowdhury, K M Azam
ABSTRACT: This paper concentrates on the protracted maritime boundary dispute with concern maritime laws. Maritime boundary dispute is a much-talked issue in the international legal arena. The countries are now becoming very much concerned with their maritime boundary for exploring and exploiting both its mineral and its food resources. But maritime boundary disputes are the barrier to use marine resources for coastal countries. So, the defined maritime boundary is necessary for every coastal state to use their maritime zones. The disputes also destroy the political harmony in international relation. Hence, the rapid settlement of maritime boundary dispute is of key importance for a peaceful coexistence of coastal states. Unfortunately, most of the disputes are delayed to be settled. United Nations Convention on the Law of the Sea is the prime international instrument which deals with the procedures of maritime boundary delimitation. This paper attempts to discuss the protracted maritime boundary disputes and maritime laws. Many of the concepts discussed in this paper can serve as guidelines for other countries that share coastlines.